NATURAL ZEOLITES STANDARDIZATION AS THE COMMODITY TOWARDS QUALITY ASSURANCE FOR ITS INDUSTRIAL USAGES - Muta’alim, Muta’alim (Jurnal Zeolit Indonesia, 2002)
The quality of zeolite deposits at some locations are not the same, whereas in its utilizations, such as the utilization for the fertilizer carriers, the standard quality of zeolite should be fulfilled, for instances the cation exchange capacity should have a minimum value of 120 meq/100 gram, particle size should be â10, +48 mesh, the zeolite grade was 50% of the tuff, and the moisture content was 8% in which its referred to the SNI 13-4696-1998, and that for the fowl and cattle food additives, the standard quality of the cation exchange capacity should be minimum value of 160meq/100gram, the particle size of â28,+100 mesh, the zeolite grade 50%, and the moisture content of 5% which is related to SNI 13-4897-1998. Nowadays, there is not all zeolites for the industry utilizations have the standard yet, whereas the each of zeolite used should reach the quality standards. The process to attain the technical specification properties of the standard quality used for the commodity is called standardization. Standardization aspects include the procedures, the technology used, the environmental aspects, and the examinations used to be accurate and accredited. Based on the standard of the technical specifications, zeolites used will then be as commodities with assured qualities.